PENGARUH MANAJEMEN SARANA PRASARANA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA UNIVERSITAS ISLAM JEMBER - jurnalpps pps; Idhotun Nashihin (Jurnal Manajerial Bisnis, 2020)
The purpose of this study is to describe the effect of infrastructure management and work discipline on employee performance at Jember Islamic University. In addition to analyzing also partially or simultaneously the influence of infrastructure management and work discipline on employee performance at the Islamic University of Jember. This research uses quantitative descriptive. The number of respondents was 124 respondents. RESEARCH RESULT. Work discipline is partial to employee performance. Management of infrastructure and work discipline positively and significantly on employee performance.Keywords: infrastructure management, work discipline, employee performance